QUALITY OF COMPUTERIZED BLAST LOAD SIMULATION FOR NON-LINEAR DYNAMIC RESPONSE ANALYSIS OF FRAMED STRUCTURES - Taye, Shifferaw; Kassahun, Abdulaziz (Zede Journal of Ethiopian Engineers and Architects, 2023)
A numerical study has been conducted to determine the quality of blast load simulation for non-linear dynamic response analysis of framed structures subjected to such loads at various stand-off distances with due consideration to the provisions and requirements of Unified Facility Criteria UFC 2005. Simulation has been carried out using a general-purpose, commercial software system and a special-purpose, blast-specific software product to assess and compare the quality of response prediction of such computational models. Nonlinear dynamic analysis has been performed using a three-dimensional model of a structure and its corresponding elasto-plastic analysis on its single-degree-of-freedom representation. The results obtained for different positions of explosive charges under the two analysis models have been presented. A comparative analysis of the results indicates that the quality of blast load simulation and associated structural response depend both on the analysis model of choice and the stand-off distances. It was concluded that the quality of response prediction by commonly available general purpose software systems is of inferior quality and that special-purpose software systems need to be implemented when dealing with generalized impulse loads as the standoff distance for the detonation is getting closer to the structure.